FESTUNG: A MATLAB / GNU Octave Toolbox for the Discontinuous Galerkin Method. Part IV: Generic Problem Framework and Model-Coupling Interface (Communications in Computational Physics, 2020)
This is the fourth installment in our series on implementing the discontinuous Galerkin (DG) method as an open source MATLAB / GNU Octave toolbox. Similarly to its predecessors, this part presents new features for application developers employing DG methods and follows our strategy of relying on fully vectorized constructsand supplying a comprehensive documentation. The specific focus of the current workis the newly added generic problem implementation framework and the highly customizable model-coupling interface for multi-domain and multi-physics simulationtools based on this framework. The functionality of the coupling interface in the FESTUNG toolbox is illustrated using a two-way coupled free-surface / groundwater flowsystem as an example application.
Keywords: Open source MATLAB / GNU Octave; local discontinuous Galerkin method; 2Dv shallow water equations with free surface; primitive hydrostatic equations; Darcy's law; coupled model.